Ablation of paroxysmal atrial fibrillation in 2015: radiofrequency or cryoenergy?. (July 2015) - Sousa, Pedro A; Boveda, Serge; Combes, Nicolas; Combes, Stéphane; Albenque, Jean-Paul
Pulmonary vein isolation is the cornerstone of paroxysmal atrial fibrillation ablation. Radiofrequency (RF) ablation is currently the most widespread technique. Recently, cryoballoon ablation has emerged as an alternative to RF ablation for paroxysmal atrial fibrillation. Until now there are no data from randomized trial comparing these two techniques. The purpose of this report was to review the pulmonary vein isolation acute success, the efficiency at follow-up and the safety of these two ablation strategies. Additionally, some considerations are made concerning the contact-force sensing RF catheters and the second-generation cryoballoon.